The Computer Use Intention (CUI) scale in education: Development, validity and reliability studies - Wong, Kung-Teck; Mokhsein, Siti Eshah; Goh, Pauline Swee Choo; Hanafi, Hafizul (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The main aim of this research was to develop an instrument to examine the intention of computer use among student teachers and provide an initial psychometric evaluation of the Computer Use Intention (CUI) scale among student teachers. The process of item generation for the CUI scale was carried out through the sequential mixed method approach. A total of 177 student teachers from a teacher education participated in this study. Based on the exploratory factor analysis (EFA) results, it yielded a four-factorial with 12 items in the CUI scale. The researchers then carried out a confirmatory factor analysis (CFA) to assess its factorial validity and reliability. Based on the findings, the CUI scale reached the minimum thresholds for acceptable scale. Convergent validity and discriminant validity of the CUI scale shows satisfactory validity and good internal consistency for all 12-item of CUI scale.